The argumentation of Al-Bashir Ibrahimi’s preaches. The Arabic: Its virtue over science and civism, and its impact on non-Arab nations as a model. - Mazouz, Abd alhalim (Milev Journal of Research and Studies, 2018)
Sheikh Al-Bashir Ibrahimi lived at a stage marked by the intensification of the conflict between French colonialism and the Algerian people. The first party tried with all its efforts to erase all the elements of identity of these colonized people in order to facilitate their control, beginning by keeping them away from all that binds them to these elements of religion and language. And the second party is mainly represented by the intellectuals of these people, including Sheikh Ibrahimi, who took upon themselves the mission of preserving the Algerian identity, with all its components, so they tried to supervise these people in various forums and places of assembly, which are available, especially mosques. And the most important of these was the association of Algerian Muslim Scholars. In this article, I tried to present the contributions of this person, who served as the Vice-President of the previous association, through a pragmatic study of the achievement of named scholar, focusing on one model, which is one of his preaches in this association, and trying to extract the elements of argumentation which took the Sheikh as way of convincing his hearers.